1989
DOI: 10.1111/j.1467-8624.1989.tb04015.x
|View full text |Cite
|
Sign up to set email alerts
|

Early School Dropout: Configurations and Determinants

Abstract: This longitudinal study examined behavioral, cognitive, and demographic factors associated with early school dropout. Follow-up assessments were completed on a sample of girls (n = 248) and boys (n = 227) who had first been seen when they were in the seventh grade. School status was determined for all living subjects; 99% of them were interviewed individually in the fifth annual test wave. Overall, 14% of the group had dropped out of school prior to completing grade 11. The clusters of males and females most v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
241
3
18

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 257 publications
(279 citation statements)
references
References 12 publications
17
241
3
18
Order By: Relevance
“…Only when combined with other risk factors (e.g., poor academic performance) does physical aggression become an antecedent for problematic developmental outcomes. In other words, it is not physical aggression itself that predicts future maladjustment, but the at-risk configuration in which physical aggression is embedded [e.g., Cairns et al, 1989a]. Social aggression, however, was not consistently related to risk factors in other areas of development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only when combined with other risk factors (e.g., poor academic performance) does physical aggression become an antecedent for problematic developmental outcomes. In other words, it is not physical aggression itself that predicts future maladjustment, but the at-risk configuration in which physical aggression is embedded [e.g., Cairns et al, 1989a]. Social aggression, however, was not consistently related to risk factors in other areas of development.…”
Section: Discussionmentioning
confidence: 99%
“…Each year independent and convergent information was gathered from the participants and the schools to determine current enrollment status [see also Cairns et al, 1989a]. School dropout was established based on whether the participant had dropped out of school prior to the end of the Grade 11.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An early investigation using a person-centered approach to examine school dropout found that youth who were characterized by multiple risk profiles (i.e., high aggression, low academic competence, affiliations with at-risk peers) had highly elevated levels of early school leaving (Cairns et al 1989). Roeser and Peck (2003) found similar results in a study of pathways and patterns of education achievement across adolescence.…”
Section: Introductionmentioning
confidence: 98%
“…This gap frequently results from an unstable intuitive knowledge-base of central concepts that should have been developed in early childhood. Academic failure during the early elementary school years can be detrimental to life course outcomes of children, with earlier school failure having the most serious and chronic consequences for children's psycho-social adjustment (Cairns, Cairns, & Neckerman, 1989;Pagani et al, 2001).…”
Section: Contextmentioning
confidence: 99%